PRELIMINARY STUDY OF THE UTILIZATION OF THE FLY ASH FROM COAL-FIRED POWER PLANT FOR IMMOBILIZATION OF RADIOACTIVE WASTE - Herry Poernomo (Indonesian Journal of Chemistry, 2011)
Preliminary study of the utilization of the fly ash from coal-fired power plant for immobilizing simulated radioactive waste has been done. The objective of this research was to study characteristics of pozzolanic material of the fly ash from coal-fired power plant as substitute of compactor material for immobilizing simulated radioactive waste. The experiment was carried out by mixing of the compactor materials such as (cement + lime), (cement + fly ash), (cement + fly ash + lime), (fly ash + lime) with Na2SO4 225 g/L and KCl 4.6 g/L as simulation of evaporator concentrate according to reference waste form no. 1 on characterization of low and medium-level radioactive waste forms in the EUR 9423-EN. Each mixture of compactor materials solidified for 14 days, 21 days, and 28 days. Solidified result was monolith, and then its compressive strength, water absorption, and porosity were tested. The experiment result showed that the best of the compactor materials on the immobilizing simulated radioactive waste was cement of 30% (wt), fly ash of 20% (wt), and lime of 20% (wt) with compressive strength of monolith of 1512.7 N/cm2. The condenser substance on the weight ratio of fly ash/lime of 20/50 - 60/10 % (wt) as pozzolanic substance could be used for immobilizing simulated radioactive waste by compressive strength of monoliths of 345 - 610.4 N/cm2. Minimum compressive strength of monolith from radioactive waste cementation according to IAEA is 320 N/cm2, hence compressive strength of monoliths from this experiment can be expressed enough well.